ТРАДИЦИИ ОБУЧЕНИЯ ЦЕРКОВНОСЛАВЯНСКОМУ ЯЗЫКУ В СТАРООБРЯДЧЕСКИХ АЗБУКАХ ИЗ ВОЙНОВСКОГО МОНАСТЫРЯ - Orzechowska, Joanna (Acta Neophilologica, 2013)
In the Old Believers’ monastery in Wojnowo a few primers survived – the remains of the school which was conducted by the nuns in the 19th and 20th century. A comparative analysis of the copies and some loose sheets which are left has shown that there are four different editions which were printed in at least two printing houses. The analysed copies are identical reprints of the earlier first edition and constitute part of an Old Russian tradition of learning to read and write which was started by Ivan Fiodorov in 1574 and continued by Jakov Zeleznikov and the Old-Ritualists printing house in Moscow.